Patient education: interpretation of medical terms as a key part of diabetes mellitus treatment - Nataliya S. Novoselova; Anna A. Mosikian; Olga Y. Martyanova; Evgenya M. Patrakeeva; Alsu G. Zalevskaya (Сахарный диабет)
Background: Only a little percent of chronically ill patients was found to follow physicians’ prescriptions. One of the reasons for this issue is misunderstanding of recommendations due to inappropriate interpretation of medical terms, contained in medical advice. Aims: The study is aimed to evaluate the quality of patient interpretation of the most frequently used medical terms in diabetes mellitus field (DM) and to evaluate the impact of misunderstanding on diabetes control. Materials and methods: 13 endocrinologists composed 2 lists of the most frequently used terms – one list for DM type 1 and one for DM type 2. We selected 10 terms for DM type 1 and 10 terms for DM type 2, mentioned by the most of participated doctors, and created 2 kinds of questionnaire for patients. Patients were to explain the terms in written if they were aware of terms’ meaning. Three independent researchers evaluated every answer according to a 0 to 10 scale, where 0 was for totally incorrect or no answer, and 10 was for a completely correct answer. Patients also filled in the forms about their social and demographic parameters. Statistical analysis was conducted with the use of Wilcoxon Test and linear regression model. Results: 89 patients with DM type 1 (27% men, HbA1c (mean±SD) 7,95±1,77%) and 86 patients with DM type 2 (27% men, HbA1c (mean±SD) 8,11±1,91%) were included into the study. Patients with type 1 DM received a greater overall score for understanding the terms than those with type 2 DM (p <0.0001) – 57.84±22.66 and 39.33±22.02 from 100, respectively. 38 (42.7%) participants with DM type 1 reported that they know all 10 terms, but only 15 (16.8%) respondents understand terms correctly. In the group of type 2 DM patients 9 (10.5%) of all answered yes for all the terms, but really know terms only 2 (2.3%) participants. In both groups, the total score of the terms knowledge did not correlate with the HbA1c level (р=0.698 and р=0.319 for type 1 and type 2 DM groups, respectively). Conclusion: The most of patients with DM do not understand relevant medical terms properly. Some patients are in the wrong belief that they have no misunderstandings with their consulting doctors. However, terms understanding does not influence on glycemic control (HbA1c level). During the medical consultation, endocrinologists should check if a patient understands their advice properly to improve understanding and compliance of patients.